Effects of sowing dates and mulching on growth and yield of wheat and weeds (Phalaris minor Retz.) - Singh, Manoj Kumar; Mishra, Amit; Khanal, Naveen; Prasad, Saroj Kumar (Bangladesh Journal of Botany, 2019)
Weed infestation, particularly Phalaris minor Retz. is a serious threat for increasing wheat productivity in Indo-Gangetic Plains of India. The primary objective of this research was to study the effect of sowing dates and mulching on the growth of wheat and weeds. In general, early sowing (November-25) exhibited less growth of P. minor, but increased weed biomass and lower wheat yields than the delayed (December-10) sowing date. Application of paddy straw, jute mat, and black polythene mulches positively increased the height, tiller count, yield of wheat; and drastically reduced weed infestation, especially the growth of P. minor. Moreover, under no weed management, delayed sowing increased the wheat yield, over earlier sowing. It was concluded that organic mulches can sustainably manage the weed infestation, particularly P. minor and increase the wheat yield.